Strontium-doped hydroxyapatite microspheres loaded with iloprost promote dentin–pulp complex regeneration - Chen, Jilong; Di, Jingyi; Yu, Qiming; Xiao, Hui; Wang, Ting; He, Li (Frontiers in Bioengineering and Biotechnology, 2026)
BackgroundVital pulp therapy (VPT) aims to preserve pulp vitality and tooth function. However, materials like calcium hydroxide and mineral trioxide aggregate have limitations in bioactivity, underscoring the need for improved biomaterials. Strontium-doped hydroxyapatite (Sr-HA) and pro-angiogenic agents have emerged as promising strategies to enhance dentin–pulp complex regeneration.MethodsHollow hydroxyapatite microspheres with 5%, 10%, and 15% Sr substitution were synthesized, and the optimal concentration was identified through Sr2+ release profiling and CCK-8-based cytocompatibility screening. Iloprost was subsequently loaded onto the selected 5% Sr-HA to obtain Ilo@Sr-HA. Human dental pulp stem cells (hDPSCs) were isolated from healthy extracted premolars using the tissue-explant method and identified by flow cytometry and multilineage differentiation assays. The identified cells were used to assess viability, ALP activity, mineralized nodule formation, and odontogenic gene expression. A bilateral rat pulp-exposure model (N = 40; n = 10/group: Blank, Dycal, Sr-HA, Ilo@Sr-HA) was established. Reparative outcomes were quantified using micro-CT and histological scoring at days 7 and 28.ResultsPreliminary screening identified 5% Sr-HA as optimal, with the best ion release and cytocompatibility. Ilo@Sr-HA showed a biphasic release and no cytotoxicity toward hDPSCs. In vitro, Ilo@Sr-HA enhanced hDPSCs proliferation and ALP activity compared with HA and Sr-HA. Mineralized nodule formation increased, with significant DMP1 and DSPP upregulation (P < 0.05). In vivo, Ilo@Sr-HA enhanced reparative dentin formation, with DV/TV reaching 38.91% at 4 weeks vs. 26.53% for Dycal (P < 0.01). Histology confirmed continuous dentin bridges in the Ilo@Sr-HA group, contrasting with incomplete structures in Dycal and Sr-HA. Lower inflammation and better pulp preservation were also observed.ConclusionIlo@Sr-HA combines Sr2+ ionic cues with iloprost’s pharmacological effects to form a bioactive microenvironment that supports pulp repair and reparative dentinogenesis. Ilo@Sr-HA is a promising material for VPT and dentin–pulp regeneration.